Experimental Effects of Acute Exercise on Prospective Memory and False Memory. Issue 4 (August 2019) - Green, David; Loprinzi, Paul D.
Research demonstrates that acute exercise can enhance retrospective episodic memory performance. However, limited research has examined the effects of acute exercise on prospective memory, and no studies have examined the effects of exercise on false memory performance. This study examined the potential effects of acute exercise on prospective memory and false memory performance. A between-group randomized controlled trial was employed, with participants (college students; Mage = 20 years) randomized into an exercise group (15-minute acute bout of treadmill walking; N = 25) or a control group (15 minutes of sitting; N = 26). Prospective memory was assessed from two laboratory and two naturalistic assessments outside the lab. False memory was assessed using a word-list trial. There were no statistically significant differences in prospective memory based on group allocation (FGroup×Time = 1.17; P = 0.32; η 2 = 0.06). However, the control group recalled more false words and had a higher rate of false memory recognition (FGroup×Time = 3.15; P = 0.01; η 2 = 0.26). These findings indicate that acute moderate-intensity aerobic exercise is not associated with prospective memory performance but provides some suggestive evidence that acute exercise may reduce the rate of false memories.